DESENVOLVIMENTO DE UM SENSOR ELETROQUÍMICO EMPREGANDO NANOFIOS À BASE DE TI DOPADO COM COBRE PARA DETECÇÃO DE GALATO DE PROPILA EM ÓLEO COMESTÍVEL - PACHECO, Jeovana Costa (2025)
Propyl Gallate (PG) is a synthetic antioxidant widely used in the food industry and has attracted the attention of researchers due to the potential risks it may pose to human health. Therefore, it is crucial to develop new analytical methods for its determination. In this context, this study describes the development of an electrochemical platform based on a carbon printed electrode (SPE) modified with nanowires (NWs) composed of titanium (Ti) and copper (Cu) for the detection of PG. The synthesis of Ti-based NWs involved varying amounts of Cu, aiming to enhance the electrochemical properties of the sensor. Interestingly, it is important to emphasize that the syntheses were carried out without the use of organic stabilizers, resulting in cleaner nanostructures. This approach aims to improve performance for electrochemical sensing, reduce costs, promote environmental compatibility and improve charge transfer efficiency, making the synthesis process ideal for the sustainable production of nanomaterials. The synthesized materials were characterized by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), cyclic voltammetry (VC) and scanning voltammetry linear (VVL). The SEM images revealed that the unmodified SPE presents a characteristic rough surface, while the surface of the SPE modified with Cu-doped Ti-based NWs showed a dense network of this material. XRD analyzes indicated that the addition of Cu affected the structure of the Ti-based NWs. Voltammograms showed an improvement in the electrochemical properties of the modified SPE after the introduction of copper. Under optimized conditions, it was found that PG can be determined over a wide concentration range from 500 pmol L⁻¹ to 5000 µmol L⁻¹. The applicability of the sensor was verified by detecting PG in soybean oil and sunflower oil samples, with excellent recovery values between 96.3% and 100.4%, indicating that the proposed sensor demonstrates good accuracy and can be applied with success in edible oil samples.